口蓋の小唾液腺に発生した基底細胞腺癌の1例 - 新村, 兆一郎; 杉山, 昌彦; 西野, 辰太郎; 小間, 義朗; 藤本, 雄大; 上嶋, 伸知 (日本口腔外科学会雑誌, 2015)
Basal cell adenocarcinoma （BCAC） is a rare tumor of the salivary gland and commonly arises in the parotid gland. It very rarely occurs in a minor salivary gland of the palate. We report the case of an 81-year-old Japanese woman with BCAC of the palatal minor salivary gland. Computed tomography and magnetic resonance imaging showed a mass （60 × 50 × 35mm） arising in the left side of the palate. The mass extended beyond the midline and invaded the maxillary sinus and pterygoid process. A biopsy was performed, and BCAC was diagnosed. Radiotherapy was administered at 2 Gy/fraction/day, and the total dose delivered to the primary tumor was 70 Gy. The lesion clinically shrank after radiotherapy. There has been no evidence of growth of the primary tumor or distant metastasis as of 24 months after radiotherapy.